"Colonisation ... in top gear": New Zealand Architecture in the 1870s - McCarthy, Christine (Architectural History Aotearoa, 2018)
The decade opened with the departure of British imperial troops from our shores, in anticipation of the end of the New Zealand Wars. This coincided with Julius Vogel’s bold plans for New Zealand public infrastructure supporting roads, railways and immigration, requiring overseas borrowing of £10 million. Part of Vogel’s motivation included the idea that employment for Māori would create peace between Māori and Pākehā.